ANALISIS GAYA BAHASA BUKU DONGENG BERGAMBAR SI KANCIL YANG CERDIK SEBAGAI ALTERNATIF BAHAN AJAR MENULIS PUISI SISWA KELAS IV SEKOLAH DASAR - Nurul Islamiyati, - (2021)
The National Centre for Competency Based Training (in Prastowo, 2014), states that teaching materials are any form of material that can be used to assist teachers or instructors in carrying out the learning process in the classroom. The learning materials of writing poetry commonly used refer to student books, student worksheets, the internet, and utilizing the environment around students. The purpose of this study is to analyze the style of language through illustrated fairy tale book Si Kancil yang Cerdik as an alternative teaching material to write poetry grade IV elementary school students. In this study using qualitative approach by applying content analysis method. The subject of this study is the style of language in illustrated fairy tale books Si Kancil yang Cerdik. The results of the study that has been done obtained 115 sentences that use the style of language in a fairy tale book. There are 19 types of language style, among which are comparative language style (parables, metaphors, personification, allegories (fables), antithesis, pleonasm and tautology, perifrasis, and correction or epanortosis) a total of 70 data, opposition language style (hiperbola, ironi, apostrof, sinisme, and sarkasme) a total of 34 data, linking language style (metonomia, synecdoke, epithet, and ellipsis) total of 10 data, and the iteration style is mesodilopsis as much as 1 data. From the data there are 7 categories that describe what the author wants to convey, such as the atmosphere, circumstances, fellings, action, figures, attitudes, and time that are then used as teaching materials in the form of handouts containing poetry writing materials, language style for teacher handles and student worksheets as an exercise in understanding language style and writing poetry. Keywords: Language Style, Teaching Materials